Sosialisasi Pemahaman mengenai UU Perlindungan Data Pribadi di Internet pada Desa Baros, Kecamatan Baros, Kabupaten Serang - Syahrul Salam; Mansur Juned; Ratu Nadia Wahyuningratna; Rahmadini Ayu Agung Utami; Ali Zafir Talmullah; Nurmasari Situmeang (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The era of the internet of things (IoT) changes activities to digital or referred to as digitization. The convenience offered by digitization has an impact on the convenience of daily activities such as administrative activities, also referred to as administrative digitization. However, there are several exchanges of this administrative data as well as opening up opportunities for digital crimes in the form of theft of personal data in the digital space. Law No. 27 concerning Personal Data Protection is necessary to address the rampant data leakage. This regulation, which has not been ratified for a month, has not yet received public attention. In fact, public attention to this regulation is needed considering that personal data crimes continue to occur. Based on this need for expansion of attention, the service team conducted a socialization of understanding of the Personal Data Protection Law on the internet. The counselling was conducted in Baros Village, Baros District, Serang Regency by involving local communities that use social media for their daily activities. The socialization activity was carried out with a series of activities in the form of a pre-test, a presentation lecture, and an evaluation in the form of a post-test distribution. The results showed that the socialization increased participants' understanding of the importance of personal data protection and the important contents of the Personal Data Protection Law.